Actor and Partner Effect of Loneliness on Episodic Memory and Verbal Fluency: A Dyadic Multilevel Analysis of Romantic Couples Across 28 Countries. (27th June 2022) - Luchetti, Martina; Ledermann, Thomas; Aschwanden, Damaris; Nikitin, Jana; O'Súilleabháin, Páraic S; Stephan, Yannick; Terracciano, Antonio; Sutin, Angelina R
Abstract: Objectives: There is evidence that loneliness is detrimental to cognitive health. Most studies, however, do not consider the association between loneliness and cognition in the context of close relationships, such as a spouse or romantic partner. This study examines loneliness, experienced by both the individual and their romantic partner, and cognitive performance. Methods: Data were from 24, 689 opposite-sex couples (49, 378 participants) from 28 countries in the Survey of Health, Aging and Retirement in Europe. Each couple participant reported loneliness and completed memory and verbal fluency tasks. A multilevel sex-stratified analysis was used to account for the nested data structure and evaluate actor and partner effects of loneliness on cognitive performance for male and female partners. Results: Consistent with the literature, there were small actor effects of loneliness on memory and verbal fluency for both males and females: A person's own loneliness was associated negatively with their cognitive performance on both tasks. There were also small partner effects: A person with a partner who was lonely tended to have worse cognitive performance above and beyond their own loneliness. Actor and partners effects were similar for male and female partners, replicated in most countries, and generally held controlling for age, education, household size, and disease burden. For memory, loneliness effects were slightly stronger among older participants. Discussion: Both the experience of loneliness and loneliness of a partner have a negative association with cognitive health.